Flat-on ambipolar triphenylamine/C60 nano-stacks formed from the self-organization of a pyramid-sphere-shaped amphiphile. Issue 4 (22nd January 2016) - Liang, Wei-Wei; Huang, Chi-Feng; Wu, Kuan-Yi; Wu, San-Lien; Chang, Shu-Ting; Cheng, Yen-Ju; Wang, Chien-Lung
Abstract : The study identified the flat-on dual-channel nano-structure and the ambipolar characteristics of a novel giant pyramid-sphere shape amphiphile. Abstract : A giant amphiphile, which is constructed with an amorphous nano-pyramid (triphenylamine, TPA) and a crystalline nano-sphere (C60 ), was synthesized. Structural characterization indicates that this pyramid-sphere-shaped amphiphile (TPA–C60 ) forms a solvent-induced ordered phase, in which the two constituent units self-assemble into alternating stacks of two-dimensional (2D) TPA and C60 nano-sheets. Due to the complexity of the molecular structure and the amorphous nature of the nano-pyramid, phase formation was driven by intermolecular C60 –C60 interactions and the ordered phase could not be reformed from theTPA–C60 melt. Oriented crystal arrays ofTPA–C60, which contain flat-on TPA/C60 nano-stacks, can be obtained via a PDMS-assisted crystallization (PAC) technique. The flat-on dual-channel supramolecular structure ofTPA–C60 delivered ambipolar and balanced charge-transport characteristics with an average μ e of 2.11 × 10 −4 cm 2 V −1 s −1 and μ h of 3.37 × 10 −4 cm 2 V −1 s −1 . The anisotropic charge-transport ability of the pyramid-sphere-shaped amphiphile was further understood based on the lattice structure and the lattice orientation ofTPA–C60 revealed from electron diffraction analyses.